2020
DOI: 10.1016/j.bjoms.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck oncological ablation and reconstruction in the COVID-19 era – our experience to date

Abstract: The COVID-19 pandemic has caused unprecedented disruption to the routine operations of healthcare services across the world. As the potential duration of the pandemic remains uncertain, the need to develop strategies to continue urgent elective services has received increasing attention. A solution adopted in the Kent, Sussex and Surrey area of England has been to create COVID-19-protected cancer hubs. The Queen Victoria Hospital is the designated hub for head and neck cancer services in the area. We report on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Testing played a huge role in various studies, with many hospitals enabling patient screening for COVID-19 symptoms upon hospital entry or pre-operatively. 3 , 7 - 38 This involved recording body temperature, checking respiratory symptoms, and taking blood tests and nasal swabs. 3 , 10 , 11 , 22 , 33 , 34 , 36 , 39 If the tests results were positive, patients were either disallowed treatment, asked to isolate/quarantine or were directed to COVID-19 outpatient clinics/admitted in to dedicated COVID-19 wards.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Testing played a huge role in various studies, with many hospitals enabling patient screening for COVID-19 symptoms upon hospital entry or pre-operatively. 3 , 7 - 38 This involved recording body temperature, checking respiratory symptoms, and taking blood tests and nasal swabs. 3 , 10 , 11 , 22 , 33 , 34 , 36 , 39 If the tests results were positive, patients were either disallowed treatment, asked to isolate/quarantine or were directed to COVID-19 outpatient clinics/admitted in to dedicated COVID-19 wards.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported the use of telehealth through videoconferencing, telephone, email, mobile phone apps and text message as a means to monitor and counsel patients. 3 , 7 - 8 , 11 - 12 , 15 - 19 , 20 - 22 , 24 , 29 , 30 , 33 - 37 , 39 - 41 , 43 , 45 , 46 , 48 - 65 , 78 This included screening, symptom checking and side effect monitoring and outpatient care. 8 , 22 , 29 , 39 , 45 , 52 - 54 These modalities of communication were significant in enabling better evaluation and follow-up of patients, as well as facilitating patient triaging and contact tracing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations